THE ROLE OF CORPORATE GOVERNANCE IN PREVENTING MISSTATED FINANCIAL STATEMENT - Siregar, Sylvia Veronica; Bachtiar, Yanivi S. (Jurnal Akuntansi dan Keuangan Indonesia, 2005)
The purpose o f our study is to empirically investigate the relation between certain corporate governance mechanisms and the likelihood o f a company having accounting problem, as evidenced by a misstatement o f its earnings. We use public listed firms in JSE as our sample, with total samples o f 160 firms-years. Our study finds that proportion o f independent board, proportion o f institutional ownership, and audit quality is significantly have negative relationship with the probability o f restatement. These results suggest that those governance mechanisms are able to prevent misstated financial misstatement. But, we find that three governance mechanisms - board size, existence o f audit committee, and block holders - do not have significant relationship with the probability o f restatement.